The late Palaeo-Indian Great Lakes : geological and archaeological investigations of late Pleistocene and early Holocene environments - Jackson, Lawrence J.; Hinshelwood, Andrew (Mercury series., 2004)
"For the first time, a series of detailed studies is available on the Late Palaeo-Indian occupations of the Great Lakes margins. These thirteen papers by prominent Canadian and American archaeologists and geological scientists will be of particular interest to anyone wishing to learn more about point typology, site disposition patterns, and geological events of this period. Editors Lawrence J. Jackson and Andrew Hinshelwood have assembled a diverse collection of articles providing an initial overview of the region from Lake Ontario to Lake Superior and beyond during this time of immense environmental change and challenge to human survival."--Jacket.